The Influence Of Long-Term Contraception Method Mobile Application On The Behavior Of Prospective Family Planning Acceptors - Diah Ulfa Hidayati; Sudirman Sudirman; Rasipin Rasipin (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Short-term contraceptive use in Indonesia still dominates. The government developed counseling method, but this program is not yet accessible to everyone. An educational media that is mobile and easily accessible is needed. This study aims to see the effect of Long-Term Contraception Method mobile application on the behaviour of prospective acceptors. This research used quasi experimental. The research subjects were couples of reproductive age in the Gunungsari Health Center. A total of 72 people were given education with applications or leaflets. Behaviour variables were measured before and after 21 days of treatment. The results showed that the application mobile long-term contraceptive method had influence on the behaviour of prospective acceptors. This application was better than the leaflet on increasing knowledge (p= 0.001), attitudes (p= 0.001), and actions (p= 0.006). This application provides complete information about the Long-Term Contraception Method and is easily accessible to users via andevice Android.